Microbiome in Healthy Women Between Two Districts With Different Air Quality Index - Wu, Yinhua; Wang, Zujin; Zhang, Yu; Ruan, Liming; Li, Ang; Liu, Xiaoyan (Frontiers in Microbiology, 2020)
Although the diversity and abundance of skin microbiome are mainly determined by intrinsic factors, including gender, age, anatomical site and ethnicity, we question whether facial microbiome could be affected by long-term exposure to airborne pollution. Using 16S rRNA gene amplicon sequencing, we analyzed the facial bacterial microbiome of healthy and young Chinese women (25~35-ys-old) between two districts with different AQI (air quality index) in Zhejiang Province. The overall microbiome structure was obviously different between these two districts. It revealed an increase of both the abundance and diversity of facial bacterial microbiome in Hangzhou (HZ) with higher AQI compared with those in Yunhe (YH) with lower AQI. LDA and Lefse analysis identified a total of 45 genera showing significantly overrepresented in the HZ group. Furthermore, PICRUSt analysis showed that functional pathways associated with metabolism of saturated fatty acid were relatively more predominant in the HZ group, whereas those with DNA repair or mitochondrial DNA replication were more predominant in the YH group. Our present data can provide useful information for further researches on the composition and function of the skin microbiome related to air pollution factors, as well as for the development of therapeutic agents targeting the microbes and their metabolites to resist damages of airborne pollutants.